Unravelling neutropenic enterocolitis: insights from gut microbiota, and intestinal barrier analyses - Natacha Kapandji; Maud Salmona; Anaïs Lemoine; Guillaume Ulmann; Julien Calderaro; Brigitte Roche; Nathalie Kapel; Lucie Biard; Etienne Lengline; Jérôme Le Goff; Christophe Rodriguez; Muriel Thomas; et al. (Experimental Hematology & Oncology)
Abstract Background Neutropenic enterocolitis (NE) is a severe digestive complication of chemotherapy, primarily affecting patients with acute myeloid leukemia (AML). We hypothesized that NE is linked to intestinal barrier dysfunction and gut dysbiosis. Methods Sixty-five AML patients undergoing induction chemotherapy were included in this prospective monocentric cohort. Among them, 26 patients (40%) were diagnosed with NE. Stool samples were subjected to bacterial load quantification (all bacteria quantitative PCR), 16s rRNA metagenomic analysis, and short-chain-fatty-acids quantification. Additionally, fecal calprotectin and human 𝛃-defensin 2 along with plasmatic inflammatory cytokines, and citrulline levels were measured. Human transcriptomic analysis was conducted on samples obtained from anatomical specimens of colectomies of NE patients. Results Gut microbiota underwent significant alterations after chemotherapy, transitioning from a diverse and balanced enterotype to enterotypes exhibiting a reduced α-diversity, an increased abundance of Enterococcus faecalis, and a decreased abundance of butyrate-producing genera, which correlated with a decreased fecal concentration of butyrate. Simultaneously, post-chemotherapy, plasma citrulline concentrations decreased indicating enterocyte damages. Finally, human transcriptomic analysis found a significant upregulation of the JAK-STAT signaling KEGG pathway in the colons of NE patients encompassing cytokines (IL-6, OSM-OSMR) that play a pivotal role in sustaining local inflammation within the digestive tract. Conclusions This work reaffirms the significant influence of chemotherapy on the gut microbiota and the integrity of the enterocyte barrier. Severe NE is marked by the development of a local inflammatory response that may be induced by the reduction in butyrate levels. Trial registration The study was registered on Clinicaltrials.gov (identifier: NCT04438278). Graphical Abstract